Suppression of IRE1α Attenuated the Fatty Degeneration in Parenteral Nutrition-Related Liver Disease (PNALD) Cell Model - Ningxun Cui; Mingling Cui; Jie Li; Xueping Zhu; Xiaoli Zhu (Gastroenterology Research and Practice)
Aims. To model the parenteral nutrition-associated liver disease (PNALD) in rat normal hepatocytes BRL and investigate the role of endoplasmic reticulum stress- (ERS-) related IRE1α signal in the process of PNALD. Methods. The BRL cells were treated with different concentrations of soybean oil emulsion (SO) to induce hepatocyte fatty degeneration. The PNALD cell disease model was further confirmed by analysis of Oil Red O staining and biochemical parameters. Next, the IRE1α was silenced by specific shRNAs via lentivirus and the role of IRE1α in anticytotoxicity and the expression level of ERS-related protein IRE1α and p-IRE1α were measured. Results. The results of Oil Red O staining indicated that the PNALD was successfully established in BRL cells and the CCK-8 data indicated which 0.6% that SO was further applied to the experiment owing to its better induction of PNALD and less toxicity to the cells. Besides, the value of biochemical parameters (TBIL, DBIL, ALT, and AST) was also elevated in the SO group compared with the NG group. After knockdown of IRE1α, the PNALD was also induced while the cells were more tolerant to SO. The less positive Oil Red O staining and reduced values of biochemical parameters were observed in the shIRE1α group when compared to the shControl, both of which accepted SO treatment. Conclusion. IRE1α was induced in PNALD cell model and suppression of IRE1α resulted in reduced steatosis in this cell disease model. Taken together, our data suggested that the IRE1α pathway may be involved in the development of PNALD.